Patient monitoring through liquid biopsies using circulating tumor DNA. Issue 5 (25th May 2017) - Ulz, Peter; Heitzer, Ellen; Geigl, Jochen B.; Speicher, Michael R.
Abstract : Tumors release components such as circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), and tumor‐derived extracellular vesicles into the circulation. Multiple studies have demonstrated that molecular information about tumors and metastases can be extracted from these factors, which are therefore frequently referred to as "liquid biopsies." Liquid biopsies allow the longitudinal monitoring of tumor genomes non‐invasively and may hence ensure that patients receive appropriate treatments that target the molecular features of their disease. Accordingly, the number of studies employing liquid biopsy based assays has been skyrocketing in the last few years. Here, we focus on three important issues, which are of high relevance for monitoring tumor genomes. First, we analyze the relation between the allele frequency of somatic tumor‐specific mutations and the tumor fraction within plasma DNA. Second, we ask how well current tumor evolution models correlate with findings in longitudinal liquid biopsy studies. And, finally, as sensitivity is one of the key challenges of mutation detection, we address the challenge of detecting mutations occurring at very low allele frequencies in plasma DNA.